2004
DOI: 10.1128/jb.186.1.146-153.2004
|View full text |Cite
|
Sign up to set email alerts
|

In Pseudomonas syringae pv. phaseolicola, Expression of the argK Gene, Encoding the Phaseolotoxin-Resistant Ornithine Carbamoyltransferase, Is Regulated Indirectly by Temperature and Directly by a Precursor Resembling Carbamoylphosphate

Abstract: Pseudomonas syringae pv. phaseolicola synthesizes a non-host-specific toxin, phaseolotoxin, and also synthesizes a phaseolotoxin-resistant ornithine carbamoyltransferase (ROCT) to protect itself from its own toxin. ROCT is encoded by argK, which is expressed coordinately with phaseolotoxin synthesis at 18°C. To investigate the regulatory mechanisms of this system, null mutants were constructed for argK, argF (encoding the phaseolotoxin-sensitive OCTase [SOCT]), and amtA (encoding an amidinotransferase involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 32 publications
(48 reference statements)
1
28
0
Order By: Relevance
“…The latter (inorganic) moiety is proposed to inactivate another repressor, R 2 , thereby derepressing argK. Thus, although temperature control of argK is indirect, the onset of resistance and toxin production are nevertheless coupled [126,194].…”
Section: Target Ornithine Carbamoyltransferase: Phaseolotoxinmentioning
confidence: 98%
See 1 more Smart Citation
“…The latter (inorganic) moiety is proposed to inactivate another repressor, R 2 , thereby derepressing argK. Thus, although temperature control of argK is indirect, the onset of resistance and toxin production are nevertheless coupled [126,194].…”
Section: Target Ornithine Carbamoyltransferase: Phaseolotoxinmentioning
confidence: 98%
“…Two genes encoding OCT activity, argF and argK, are present in the producer [170] and one of them (argK, encoding ROCT) is located within the phaseolotoxin-biosynthetic cluster [1]. According to one model [126], temperature downshift is sensed in P. syringae pv. phaseolicola by an unknown mechanism that inactivates a transcriptional repressor, R 1 .…”
Section: Target Ornithine Carbamoyltransferase: Phaseolotoxinmentioning
confidence: 99%
“…However, only weak binding of the putative repressor protein to the TRR sites in argK has been postulated (23). Furthermore, the TRR domains in argK may not be involved in its regulation since we have shown that this gene is not directly regulated by temperature but most likely is regulated through induction mediated by a precursor of phaseolotoxin resembling carbamoylphosphate (11). Therefore, there seem to be two proteins that bind to the TRR, one protein which binds tightly to strictly temperature-regulated promoters and a different protein which acts as a repressor for argK with only weak binding to the TRR and which is not temperature regulated.…”
mentioning
confidence: 94%
“…It has been shown previously that in fact argK is not directly regulated by temperature but most likely is regulated by a precursor of phaseolotoxin resembling carbamoylphosphate (11). In Pseudomonas aeruginosa argF is repressed when growth occurs in media that provide high levels of exogenous arginine, such as King's medium B (KB), together with the repressor protein ArgR, which also represses the carAB operon involved in carbamoylphosphate biosynthesis (20,21).…”
mentioning
confidence: 99%
“…Likewise, phaseolotoxin production is thermoregulated in P. syringae pv. phaseolicola by a process involving a small, noncoding RNA and, potentially, a metabolic intermediate, although the details of this process are currently unknown (21)(22)(23). More generally, it is unknown whether there are any conserved global thermoregulators in P. syringae similar to those described in E. coli.…”
mentioning
confidence: 99%